Investigation of thermal properties of carbon nanotubes and carboxyl group - functionalized carbon nanotubes - R.G. Abaszade; E.M. Aliyev; M.B. Babanli; V.O. Kotsyubynsky; R.I. Zapukhlyak; A.G. Mammadov; H.F. Budak; A.E. Kasapoglu; E. Gür; T.O. Margitych; M.O. Stetsenko (Фізика і хімія твердого тіла, 2023)
Thermal properties characterizations for carbon nanotubes (CNTs), carboxyl group-functionalized carbon nanotubes (FCNT), and graphite were presented in the paper. TGA/DSC and TEM techniques were used for characterization. The features of TGA characteristics transformation for synthesized carbon nanomaterials were investigated. The specific heat capacities of the samples at a constant pressure increased as the temperature increased.